2014
DOI: 10.1007/s10346-014-0514-9
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic debris flows triggered by a 4 July 2013 rainfall in Shimian, SW China: formation mechanism, disaster characteristics and the lessons learned

Abstract: Catastrophic debris flows triggered by a 4 July 2013 rainfall in Shimian, SW China: formation mechanism, disaster characteristics and the lessons learned Abstract On 4 July 2013, three catastrophic debris flows occurred in the Hougou, Majingzi, and Xiongjia gullies in Shimian county and produced debris dams and river blockages, resulting in serious casualties and huge economic loss. Though debris flows have been identified prior to the catastrophic events, their magnitudes and destructive power were far beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…García-Martínez and López 2005;Casagli et al 2006;Tang et al 2012;Cevaso et al 2014;Chen et al 2014;Ni et al 2014;Yang et al 2015). For example, in December 1999, extreme rainfall on the northern Venezuelan coast triggered a disastrous debris flow, which caused about 1,500 fatalities and the destruction of 23,000 houses (García-Martínez and López 2005).…”
Section: Introductionmentioning
confidence: 99%
“…García-Martínez and López 2005;Casagli et al 2006;Tang et al 2012;Cevaso et al 2014;Chen et al 2014;Ni et al 2014;Yang et al 2015). For example, in December 1999, extreme rainfall on the northern Venezuelan coast triggered a disastrous debris flow, which caused about 1,500 fatalities and the destruction of 23,000 houses (García-Martínez and López 2005).…”
Section: Introductionmentioning
confidence: 99%
“…8c), as the magnitude of the 2010 debris flow exceeded the mitigation capacity. Such mitigation might create a false sense of security and possibly leading to more losses (Olugunorisa, 2009;Cigler, 2009). It might be not beneficial to start installing mitigation measures right after an earthquake, as the magnitude and frequency of mass-movement hazards might be too costly to mitigate.…”
Section: Exposure and Mitigationmentioning
confidence: 99%
“…The most commonly witnessed cases include landslides forming barrier lakes which later cause outburst floods Dong et al, 2011) or debris flows (Hu and Huang, 2017). Moreover the debris flows can result in river damming and riverbed rising (Ni et al, 2014;Tang et al, 2012;Fan et al, 2019b), causing floods. A comprehensive summary of postearthquake hazard chains was made by Fan et al (2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The rainfall intensity recorded by the downstream rain gauge was 1 mm/h or less and the duration was quite short, which is in line with the memory of the local citizen in the downstream area who witnessed the flow, suggesting the rain gauge was working well; however, it seems impossible for a low-intensity short-duration rainfall to generate surface water runoff, let alone entrain sediment and trigger debris flows. In the Hengduan Mountains, isolated convective rainfall is common and has been found to be an important trigger of debris flows in this area (Tang et al, 2011;Ni et al, 2014); in addition, rainfall intensity has also been found to increase with elevation in the Jinsha Basin (Tan et al, 1994). Here, we speculate that the three post-wildfire debris flows in 2014 were triggered by isolated convective rainfall and that the rain gauges down slope can definitely record the triggering rainfall.…”
Section: Rainfall Thresholdmentioning
confidence: 99%